Fibromyalgia Assessment Screening Tools (FAST) Based on Only Multidimensional Health Assessment Questionnaire (MDHAQ) Scores as Clues to Fibromyalgia. Issue 8 (22nd August 2019) - Schmukler, Juan; Jamal, Shakeel; Castrejon, Isabel; Block, Joel A; Pincus, Theodore
Abstract : Objective: The study was designed to develop fibromyalgia assessment screening tool (FAST) indices based only on multidimensional health assessment questionnaire (MDHAQ) scores as clues to fibromyalgia (FM), analyzed for possible agreement with the 2011 FM criteria. Methods: All patients with all diagnoses complete an MDHAQ at each visit in routine care. The MDHAQ includes scores for physical function, pain, global assessment, fatigue, self‐report painful joint count, and a 60‐symptom checklist. MDHAQ items similar or identical to the 2011 FM criteria symptom severity scale (SSS) and widespread pain index (WPI) components of a polysymptomatic distress scale (PSD) were compiled into continuous MDHAQ‐FM‐SSS, MDHAQ‐FM‐WPI, and MDHAQ‐FM‐PSD indices. Ten candidate MDHAQ scores were analyzed against the 2011 FM criteria using descriptive statistics, Spearman correlations, kappa statistics, and receiver operating characteristic curves for the area under the curve (AUC). MDHAQ candidate variables with the highest AUC were compiled into cumulative MDHAQ‐FAST indices of three (FAST3) or four (FAST4) scores. Results: The highest AUCs among MDHAQ scores were seen for symptom checklist, painful joint count, fatigue, and pain, which are included in FAST4; FAST3‐F excludes pain, and FAST3‐P excludes fatigue. AUCs for FAST3‐P, FAST3‐F, and FAST4, as well as continuous MDHAQ‐FM scores, all were greater than 0.92, indicating excellent criterion validity. Kappa statistics versus the 2011 criteria were 0.63‐0.68, higher than 0.41‐0.47 versus physician ICD‐10 diagnoses. Conclusion: Pragmatic FAST3, FAST4, and MDHAQ‐FM indices are similar to FM criteria to screen for FM in routine care. It is more feasible to collect the same MDHAQ, which is informative in all rheumatic diseases studied, from each patient than to ask different patients with different diagnoses to complete different questionnaires.